Schistosomiasis Pulmonary Arterial Hypertension - Sibomana, Jean Pierre; Campeche, Aloma; Carvalho-Filho, Roberto J.; Correa, Ricardo Amorim; Duani, Helena; Pacheco Guimaraes, Virginia; Hilton, Joan F.; Kassa, Biruk; Kumar, Rahul; Lee, Michael H.; Loureiro, Camila M. C.; Mazimba, Sula; et al. (Frontiers in Immunology, 2020)
Pulmonary arterial hypertension (PAH) is a disease of the lung blood vessels that results in right heart failure. PAH is thought to occur in about 5-10% of patients with hepatosplenic schistosomiasis, particularly due to S. mansoni. The lung blood vessel injury may result from a combination of embolization of eggs through portocaval shunts into the lungs causing localized Type 2 inflammatory response and vessel remodeling, triggering of autonomous pathology that becomes independent of the antigen, and high cardiac output as seen in portopulmonary hypertension. The condition is likely underdiagnosed as there is little systematic screening, and risk factors for developing PAH are not known. Screening is done by echocardiography, and formal diagnosis requires invasive right heart catheterization. Patients with Schistosoma-associated PAH show reduced functional capacity and can be treated with pulmonary vasodilators, which improves symptoms and may improve survival. There are animal models of this disease that might help in understanding disease pathogenesis and identify novel targets to screen and treatment. Pathogenic mechanisms include Type 2 immunity and activation and signaling in the TGF-β pathway. There are still major uncertainties regarding Schistosoma-associated PAH development, course and treatment.